Preparation and integrated application of defect-structure iron-based MOF with extraction and photo-Fenton catalysis functions

By constructing the iron-based MOF material PNM-101 with defective structure, and combining solid-phase microextraction and photo-Fenton degradation technology, the problem of efficient enrichment of triclosan in complex food matrices and analysis of degradation products was solved, achieving efficient and integrated enrichment and detection effects, and significantly reducing the toxicity of degradation products.

CN121060618APending Publication Date: 2025-12-05SHANXI PROVINCIAL INSPECTION & TESTING CENT (SHANXI PROVINCIAL INST OF STANDARDS & METROLOGY TECH) +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511245585.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-02
Publication Date
2025-12-05

AI Technical Summary

Technical Problem

Existing technologies struggle to achieve efficient enrichment of triclosan and accurate analysis of its degradation products, especially in complex food matrices. Furthermore, existing MOF materials exhibit limited degradation efficiency and enrichment capacity in photo-Fenton reactions.

Method used

By constructing the iron-based MOF material PNM-101 with defective structure, and combining solid-phase microextraction and photo-Fenton degradation technology, PNM-SSW fibers were prepared for use in the SPME device to achieve integrated enrichment and detection.

Benefits of technology

It achieves efficient visible light Fenton degradation and enrichment detection of triclosan. In the integrated mode, the enrichment factor reaches 5000, with a wide linear range, low detection limit, good reusability, and significantly reduced toxicity of degradation products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 121D5C9A-7254-4ABF-A91C-5B40AA8B2CEB
    Figure 121D5C9A-7254-4ABF-A91C-5B40AA8B2CEB
  • Figure 1FCD2ECD-DEA4-4B31-A8BF-2E0577610514
    Figure 1FCD2ECD-DEA4-4B31-A8BF-2E0577610514
  • Figure 215441D9-9C5E-4FDC-BADA-2F33A777CC70
    Figure 215441D9-9C5E-4FDC-BADA-2F33A777CC70
Patent Text Reader

Abstract

The invention belongs to the field of material preparation and detection and control of organic pollutants in food, relates to the technical field of functional modification based on a specific metal organic framework material and application of the functional modification, and particularly discloses a controllable preparation method of a bifunctional PABA-NH2-MIL-101 (Fe) composite material (PNM-101) with a defect structure. According to the invention, the obtained PNM-101 material is successfully loaded on the surface of a stainless steel fiber carrier to construct a solid phase microextraction (SPME) device, and is coupled with a gas chromatography-flame ionization detector (GC-FID) system to develop a novel high-sensitivity enrichment detection method for organic pollutants. On the basis, PNM-101 is creatively used as a high-efficiency catalyst, and a photo-Fenton catalytic degradation system driven by visible light is constructed. Meanwhile, the PNM-101 stainless steel fiber is utilized to realize effective separation and enrichment of degradation products. Through system integration of the technical scheme, a whole-process integrated technical platform for visible light Fenton degradation of organic pollutants in food, directional enrichment detection of target objects and synchronous analysis of degradation products is successfully established.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the field of material preparation and detection and control of organic pollutants in food, and particularly relates to a preparation method and application of a defective structure iron-based MOF material PNM-101. BACKGROUND

[0002] Organic pollutants are a kind of semi-volatile synthetic chemicals with high environmental persistence, bioaccumulation and long-distance migration potential, which mainly come from industrial activities, agricultural application and consumer product use. This kind of pollutants can enter environmental media through atmospheric deposition, water flow and other ways, and undergo biological amplification effect along the food chain, and finally pose a serious threat to human health through dietary exposure.

[0003] Taking triclosan, which is widely used as an antibacterial agent, as an example, it is commonly found in plastic packaging, medical supplies and personal care products. Due to its bioaccumulation and non-degradability, it is easy to remain in various environmental media. Triclosan can enter the food chain through water circulation and agricultural raw material pollution, especially in the production process of food such as vinegar, liquor and beverage which mainly use liquid fermentation. If contaminated water sources or raw materials are used, triclosan residues may exist in the final product. Due to its low concentration in food matrix, complex sources and limited removal efficiency of existing purification technology for trace pollutants, the detection and analysis of triclosan in food face great challenges. Therefore, it is of great practical significance to develop efficient enrichment and detection methods for organic pollutants such as triclosan, study the migration and transformation rules of organic pollutants in food processing, and establish a degradation product monitoring strategy suitable for complex matrix systems such as vinegar, in order to ensure food safety and promote the sustainable development of food industry.

[0004] Because the degradation products of pollutants may have secondary hazard risks, the degradation products are usually low in concentration and the degradation liquid matrix is complex, so it is difficult to accurately analyze them by conventional analysis methods. The existing integrated mode mainly focuses on the degradation and detection of pollutants, and fails to use the established enrichment analysis method for the analysis of degradation products. Therefore, an integrated mode integrating pollutant degradation, enrichment detection and degradation product analysis is urgently needed.

[0005] MOFs have high porosity, large specific surface area and rich metal sites, and are widely used in catalysis, energy and separation fields, and are ideal materials for building an integrated mode. Among them, MIL-101 (Fe) has rich Fe-O clusters, which can enhance the light absorption of the material and promote the separation of photo-generated carriers in the material. This feature can accelerate the Fenton reaction of Fe 3+ / Fe 2+The valence state cycle promotes the rapid generation of strong oxidizing free radicals ·OH, and improves the Fenton oxidation rate. At the same time, it has a large cage structure, which can realize the rapid mass transfer and enrichment of EDCs in the water environment. Moreover, the good water stability and thermal stability make MIL-101 (Fe) can be used as a coating material to prepare SPME fibers, combined with high-sensitivity instruments such as GC, to realize the integration of sampling, enrichment and injection of target substances. However, due to the wide band gap, MIL-101 (Fe) is difficult to efficiently degrade EDCs with strong stability. In addition, during the degradation of EDCs, the concentration of some degradation products is low, and the classic MIL-101 (Fe) has certain limitations in adsorption capacity, and cannot realize the precise enrichment and effective analysis of these low-concentration degradation products. Therefore, it is necessary to further modify MIL-101 (Fe) to enhance its degradation and enrichment performance.

[0006] Defect engineering is a method of improving material performance by introducing and controlling defects in the material. For MOFs, defects can be constructed by ion doping, ligand adjustment, and changes in synthesis conditions, etc., to enhance the photoactivity of MOFs, improve the separation efficiency of photo-generated carriers, increase active sites, and adjust the pore structure. Among them, ligand doping can form unsaturated coordination of metal sites inside the MOFs, thereby exposing empty orbitals. These empty orbitals can accept electrons and exhibit Lewis acidity, which can reduce the reaction activation energy and enhance the catalytic performance of the material. At the same time, unsaturated coordination can also lead to changes in the framework structure of MOFs, resulting in larger pores that are beneficial to the efficient enrichment of target substances by the material. Therefore, by adjusting the ligand to construct a defect structure, it is expected to realize the simultaneous improvement of the degradation and enrichment dual functions of MIL-101 (Fe). SUMMARY

[0007] In view of the problems in the prior art, the present application provides a preparation method of a dual-functional PNM-101 material with a defect structure combining solid-phase microextraction and Fenton degradation, and its application in Fenton degradation and solid-phase microextraction enrichment detection.

[0008] The present application provides a preparation method of a dual-functional PNM-101 material with a defect structure. The specific steps include: FeCl3, NH2-BDC and p-aminobenzoic acid (PABA) were weighed into a centrifuge tube containing N,N-dimethylformamide (DMF). The mixed solution was then shaken and ultrasonicated until clear, transferred to a stainless steel autoclave, and heated at a temperature of 383 K. After the autoclave was cooled to room temperature, the product was washed with DMF and ethanol, respectively, collected by centrifugation, and placed in a vacuum dryer at a temperature of 333 K. The resulting dark brown PNM-101 powder was ground and stored for use.

[0009] In an embodiment, the FeCl3 is added in an amount of 480-490 mg, the NH2-BDC is added in an amount of 540-550 mg, and the p-aminobenzoic acid is added in an amount of 410-420 mg.

[0010] In an embodiment, the heating time at a temperature of 383 K is 20-24 h, and the vacuum drying time at a temperature of 333 K is 10-12 h.

[0011] The present application provides a method for preparing PNM-101 coated fiber PNM-SSW. The specific steps include: after the stainless steel wire (SSW) is immersed in aqua regia for corrosion, it is ultrasonically washed with water and EtOH, respectively, naturally dried, immersed in an adhesive, and then taken out and adhered with PNM-101 powder. The PNM-coated SSW is placed in an oven for curing, and the operation is repeated twice. After the curing step is completed, the PNM-SSW is placed in a GC inlet at a temperature of 300 o C for 1 h to obtain PNM-101 coated fiber PNM-SSW.

[0012] In an embodiment, the adhesive is prepared by uniformly mixing and ultrasonically treating 1.2-1.5 g of plane sealant with 2.4-3.0 mL of toluene.

[0013] In an embodiment, the temperature for curing the PNM-coated SSW in the oven is 110-120 °C, the first curing time is 25-30 min, and the second curing time is 3-3.5 h.

[0014] The present application provides related applications of PNM-101 material in photo-Fenton degradation and solid phase microextraction.

[0015] The present application establishes a method for SPME enrichment and analysis of organic pollutants by preparing a bifunctional PNM-101 material with a defect structure, fixing it on a stainless steel fiber to assemble an SPME device, and combining it with a GC-FID.

[0016] The application establishes a photo-Fenton degradation system of organic pollutants with PNM-101 as a catalyst, and PNM-SSW is used for separation, enrichment and detection of degradation products.

[0017] Compared with the prior art, the application has the following beneficial effects: 1. The construction of an integrated mode of visible light Fenton degradation, enrichment detection and enrichment analysis of degradation products of organic pollutants is realized.

[0018] 2. The synthesized PNM-101 has a larger average pore size, good thermal stability and better photoelectric performance.

[0019] 3. The enrichment factor of the constructed SPME method for the organic pollutant triclosan can reach more than 5000, has a linear range of 1 µg / L~1500 µg / L, a detection limit of 0.047 µg / L and a quantification limit of 0.157 µg / L, and also has a standard addition recovery of 90.0%~112.2% and an RSD value of 6.7%~9.6% for drinking water source water samples.

[0020] 4. The prepared PNM-SSW can be reused for more than 200 times.

[0021] 5. The degradation liquid of PNM-SSW at different time periods is subjected to enrichment analysis, and 3 possible degradation paths are proposed by combining DFT calculation. The results of ECOSAR and T.E.S.T. evaluation show that the toxicity and biological enrichment factor of the degradation products of the organic pollutant triclosan are significantly reduced. BRIEF DESCRIPTION OF DRAWINGS

[0022] Figure 1 PNM-101 and NM-101 are schematic diagrams of preparation processes; Figure 2 PNM-SSW is a schematic diagram of a preparation process of a fiber; Figure 3 PNM-101 and PNM-SSW are SEM images of surface morphologies, wherein (A) is an SEM image of PNM-101 and (B) is an SEM image of NM-101; (C) is an element mapping atlas of PNM-101; (D) is an SEM image of SSW after etching and (E) is an SEM image of PNM-SSW; (F) is a real object image of SSW, (G) is a real object image of SSW after etching and (H) is a real object image of PNM-SSW; Figure 4 NM-101 and PNM-101 are XRD diffraction patterns; Figure 5 NM-101 and PNM-101 are thermogravimetric curves; Figure 6(A) UV-vis DRS spectra, (B) XPS-VB spectra, (C) band structure schematic diagram, (D) transient photocurrent response curves and (E) Nyquist impedance plots of NM-101 and PNM-101; Figure 7 Effects of PNM-SSW solid phase microextraction conditions on the extraction efficiency of triclosan, wherein (A) extraction time; (B) desorption temperature; (C) desorption time; (D) stirring rate and (E) pH value on the extraction effect of triclosan; (F) verification of the effect of extraction time on the extraction effect of triclosan; Figure 8 Effect of PNM-SSW use times on the extraction effect of triclosan Figure 9 Condition optimization of PNM-101 visible light Fenton degradation system, wherein (A) the effect of different initial H2O2 concentrations on the visible light Fenton degradation of triclosan and (B) the corresponding pseudo-first-order kinetic fitting curve; (C) the effect of different PNM-101 dosages on the visible light Fenton degradation of triclosan and (D) the corresponding pseudo-first-order kinetic fitting curve; Figure 10 Effect of different materials and degradation systems on the degradation of triclosan, wherein (A) the effect of different systems on the visible light Fenton degradation of triclosan and (B) the corresponding pseudo-first-order kinetic fitting curve; (C) the effect of different catalysts on the visible light Fenton degradation of triclosan and (D) the corresponding pseudo-first-order kinetic fitting curve; Figure 11 Results of PNM-SSW collaborative GC-MS analysis of degradation products, wherein (A) is the analysis result using PNM-SSW enrichment and (B) is the analysis result using direct injection; (C) is the concentration change of degradation product 2,4-DCP; (D) is the mass spectrum of triclosan and (E) is the mass spectrum of 2,4-DCP; Figure 12 T.E.S.T. predicted (A) rat oral LD 50 and (B) bioconcentration factor of triclosan and its degradation products. DETAILED DESCRIPTION

[0023] The technical solutions of the present application will be described below in conjunction with the embodiments of the present application, and the methods are all conventional methods unless otherwise specified, and the raw materials can be obtained from public commercial channels unless otherwise specified.

[0024] Example 1 A preparation method of a PNM-101 material, comprising the following steps: As Figure 1As shown, 486 mg of FeCl3, 543 mg of NH2-BDC, and 414 mg of PABA were weighed and added to a centrifuge tube containing 30 mL of DMF. The mixture was then thoroughly shaken and sonicated until clear, transferred to a 50 mL stainless steel autoclave, and maintained at 383 K for 24 h. After the autoclave cooled to room temperature, the product was washed with DMF and EtOH respectively, collected by centrifugation, and then vacuum-dried at 333 K for 12 h. Finally, the resulting dark brown PNM-101 powder was ground, dried, and stored for later use.

[0025] Example 2 The preparation of PNM-101 coated fiber PNM-SSW includes the following steps: like Figure 2 As shown, one end of the SSW was immersed in aqua regia for 10 min to obtain a rough surface, followed by ultrasonic washing with water and EtOH for 30 min each. 1.5 g of surface sealant was placed in a test tube and 3.0 mL of toluene was added. The mixture was thoroughly stirred and ultrasonicated until homogeneous to obtain the adhesive. The etched end of the washed and air-dried SSW was immersed in the adhesive for 10 s and then pulled out. Excess adhesive was scraped off with a 10 µL pipette tip. The adhesive-coated end of the SSW was then inserted into a test tube containing PNM-101 powder, rotated back and forth several times, and then removed, with excess powder shaken off. Finally, the PNM-coated SSW was placed in a 120 °C oven for curing for 30 min. This process was repeated twice, with the final curing time being 3 h. After curing, the PNM-SSW was assembled into a microsyringe and aged at 300 °C for 1 h at the GC inlet.

[0026] Comparative Example 1 Preparation of NM-101 and NM-SSW extraction needle The preparation steps for NM-101 are the same as those for PNM-101, except that 543 mg NH2-BDC and 414 mg PABA in Example 1 are replaced with 1086 mg NH2-BDC.

[0027] NM-SSW was prepared using the same method as in Example 2, except that PNM-101 powder was replaced with NM-101 powder.

[0028] Example 3 Analysis of PNM-101 material and PNM-SSW surface morphology The surface morphology of the prepared PNM-101 and PNM-SSW was characterized by SEM. Figure 3As shown in A, NM-101 presents a regular octahedron configuration with a particle size of about 100 nm-300 nm. The average particle size of PNM-101 is not much different from that of NM-101 and still maintains a regular octahedron structure Figure 3 B), indicating that the doping of PABA has no effect on the geometric structure of PNM-101. Compared with NM-101, the defect structure caused by the introduction of PABA and the unsaturated coordination with Fe sites leads to the formation of structures similar to etching holes on the surface of PNM-101. As can be seen from the element mapping Figure 3 C), the four elements Fe, O, C and N are uniformly distributed in PNM-101. In addition, it can be seen from the Fe element mapping that Fe is abundant in PNM-101, which provides a large number of active sites for the Fenton reaction. Figure 3 D is the SSW fiber after aqua regia corrosion, the surface is rough but the uniformity of the diameter has not changed significantly. Figure 3 E, after the material coating, the surface roughness of PNM-SSW increases significantly, and the diameter increases from the original 226.7 µm to 239.4 µm, and the coating thickness is about 15.4 µm. Figure 3 (F-H) shows the actual situation of SSW fiber after different treatment steps. SSW initially presents a metallic luster (F), after corrosion, the luster decreases due to the increase of surface roughness (G), and the PNM-SSW after material coating and aging presents a black surface (H). Figure 3 F), after corrosion, the luster decreases due to the increase of surface roughness (G), and the PNM-SSW after material coating and aging presents a black surface (H). Figure 3 G), and the PNM-SSW after material coating and aging presents a black surface (H). Figure 4 H).

[0029] Example 4 Crystal structure analysis of PNM-101 The crystal structures of NM-101 and PNM-101 were analyzed by XRD, and the results are shown in Figure 5 The corresponding diffraction peak positions in the PNM-101 spectrum shift to higher angles relative to NM-101, and there is a decrease in crystallinity. The doping of PABA causes the growth termination of part of the PNM-101 skeleton, thereby affecting the growth of the crystal structure.

[0030] Example 5 Thermal stability analysis of PNM-101 As shown in Figure 6 When the highest temperature that the SPME coating can withstand in the experiment is reached, 300 °C, the mass of PNM-101 still remains at 77.5% of the original. Since the temperatures at which the weight loss rates of the two materials reach the maximum value (420 °C) are significantly higher than 300 °C, it can be considered that PNM-101 has good thermal stability and meets the requirements of GC high temperature desorption.

[0031] Example 6 Photoelectric performance analysis of PNM-101, the influence of PABA doping on the light absorption performance and energy band structure of the material was evaluated by UV-vis DRS and XPS-VB.

[0032] As shown in Figure 6 (A-B), NM-101 and PNM-101 both showed good light absorption activity in the range of 200 nm~800 nm in the UV-vis DRS spectrum, and the absorbance of PNM-101 was stronger in the determination range. Through analysis of the XPS-VB spectrum, the EVB (or HOMO) of NM-101 and PNM-101 was 1.18 eV and 1.05 eV, respectively.

[0033] As shown in Figure 6 (C), the conduction band potential of PNM-101 can still meet the material itself through the reduction of photo-generated electrons to Fe 3+ , promoting the progress of Fenton reaction.

[0034] As shown in Figure 7 (D), the transient photocurrent response curves of the two materials showed that the photocurrent intensity of PNM-101 was larger, indicating that the separation efficiency of photo-generated carriers in PNM-101 was higher. In addition, according to the EIS results, the introduction of PABA reduced the charge transfer resistance of PNM-101. The above results showed that the construction of coordination defects in PNM-101 promoted the effective separation of photo-generated carriers, which was beneficial to the improvement of the efficiency of photo-Fenton degradation.

[0035] Example 7 Establishment of PNM-SSW solid phase microextraction method (1) Optimization of extraction time In order to study the adsorption and desorption equilibrium of PNM-SSW fiber to triclosan, different extraction times were set to explore their influence on the extraction effect. As shown in Figure 7 A, the peak area of triclosan began to increase from 10 min and reached the maximum at 30 min, and there was no significant change in the peak area of triclosan after 30 min, so 30 min was selected as the best extraction time.

[0036] (2) Optimization of desorption temperature of GC injection port The desorption temperature of GC injection port may affect the response strength of triclosan, so different desorption temperatures were set to explore their influence on the extraction effect. As shown in Figure 7 B, the peak area of triclosan began to increase from 260 o C and reached the maximum peak area at 290 o C, and the peak area of triclosan began to decrease at 300 oThe peak area of triclosan at time C did not change significantly. To extend the service life of PNM-SSW, a lower temperature of 290 o C was selected as the optimal desorption temperature.

[0037] (3) Optimization of desorption time The length of desorption time may affect the degree of triclosan desorption, so different desorption times were set to explore their effects on extraction. As shown in Figure 7 C, the maximum peak area was reached at a desorption time of 5 min, so 5 min was selected as the optimal desorption time.

[0038] (4) Optimization of stirring rate Stirring can effectively improve the extraction kinetics of triclosan and shorten the adsorption-desorption equilibrium time of PNM-SSW for triclosan. Therefore, the effects of different stirring rates on extraction were explored. As shown in Figure 7 D, the peak area of triclosan increased continuously from 500 rpm and reached the maximum peak area at 800 rpm. After 800 rpm, the peak area of triclosan decreased slightly. Therefore, 800 rpm was selected as the optimal stirring rate.

[0039] (5) Optimization of pH value Changes in pH value can affect the form of triclosan in solution, thereby changing the extraction effect of PNM-SSW on it. As shown in Figure 8 E, when the pH value of the solution gradually increased from 3 to 7, the enrichment effect of PNM-SSW on triclosan gradually improved. When the pH value continued to increase to 9, the enrichment effect of triclosan decreased significantly. Since the measured pH value of the triclosan solution without adjusting the pH was close to 7 and the peak area difference was not large, it was decided not to adjust the extraction pH value in the subsequent experiments.

[0040] Example 8 Evaluation of the recyclability of PNM-SSW fibers The recyclable number of times of PNM-SSW fibers was investigated to evaluate their stability and application potential. As shown in Figure 9 , the 111th was the maximum peak area that PNM-SSW could reach after the optimization of the conditions, and the enrichment capacity of PNM-SSW fibers basically maintained at a stable level. When used for the 200th time, the peak area of triclosan only decreased by 7.13%, indicating that PNM-SSW had good stability and application potential.

[0041] Example 9 Construction of PNM-101 visible light Fenton degradation system, in order to achieve the best visible light Fenton degradation efficiency of PNM-101 for triclosan, the initial H2O2 concentration and material dosage were optimized.

[0042] (1) Optimization of different initial H2O2 concentrations Figure 9 The effect of different initial H2O2 concentrations on the degradation efficiency of triclosan is shown in A. When the initial H2O2 concentration is 3 mM, 6 mM, 9 mM, 12 mM and 15 mM, the degradation rate of triclosan is 92.8%, 97.5%, 99.7%, 99.2% and 99.8%, respectively. Figure 9 The degradation rate constant k = 0.0779 min -1 at 9 mM concentration in B is higher than that at other initial H2O2 concentrations except 15 mM. Since the degradation rate of 15 mM relative to 9 mM does not increase much, 9 mM is chosen as the optimal condition for subsequent optimization.

[0043] (2) Optimization of different material dosages The effect of different material dosages on the degradation of triclosan is shown in Figure 9 C. When the dosage is 0.02 g / L, 0.06 g / L, 0.10 g / L, 0.14 g / L and 0.18 g / L, the degradation rate of triclosan is 69.1%, 96.7%, 98.9%, 99.6% and 99.3%, respectively. When the material dosage increases to 0.06 g / L, the degradation rate of triclosan reaches more than 95% and reaches the maximum at a dosage of 0.14 g / L. Figure 10 The degradation rate is the fastest at 0.14 g / L (k = 0.0772 min -1 ) in D, so 0.14 g / L is chosen as the optimal material dosage.

[0044] Example 10 Effect of different materials and degradation systems on the degradation of triclosan In order to understand the performance improvement of PNM-101 in visible light Fenton degradation of triclosan, the degradation of triclosan in different degradation systems and different materials was explored.

[0045] As shown in Figure 10 A, the degradation rate of the visible light Fenton system (PNM-101 + H2O2 + light) is 99.7%, higher than that of other systems studied.

[0046] As shown in Figure 10 B, the degradation rate constant (k = 0.0772 min -1 ) of the visible light Fenton system is 0.0772 min -1 , 0.0022 min -1 and 0.0045 min-1 The degradation efficiency of the photo-Fenton system was significantly improved, being 12.9 times, 33.1 times, and 17.2 times higher than that of other systems.

[0047] The degradation performance of NM-101 and PNM-101 in the visible light Fenton system is as follows: Figure 11 As shown in Figure C, NM-101 achieved a triclosan degradation rate of 95.3%, which is not significantly different from PNM-101. However... Figure 11 The degradation rate constant of PNM-101 shown in Figure D can reach that of NM-101 (k = 0.0406 min). -1 The result shows that the unsaturated coordination and defect structure generated by PABA doping effectively improves the visible light Fenton catalytic performance of PNM-101.

[0048] Example 11 SPME-assisted GC-MS enrichment analysis of degradation products The GC-MS results obtained by extracting and analyzing the degradation solution at different time points using PNM-SSW are as follows: Figure 11 As shown in Figure A, a distinct peak appeared at approximately 6.849 min in the analytical chromatogram of all samples during the degradation process. Comparison with the NIST database revealed that this peak corresponds to 2,4-dichlorophenol (2,4-DCP). Figure 11 As shown in B, PNM-SSW enrichment injection eliminated most of the interference from impurity peaks, exhibiting significant triclosan and 2,4-DCP signals. This is attributed to the good selectivity and high enrichment factor of PNM-SSW. Furthermore, Figure 12 The concentration of 2,4-DCP shown in C reached its maximum after 20 min of degradation, and its peak area gradually decreased as degradation progressed, indicating that PNM-101 can effectively degrade triclosan and its intermediate products.

[0049] Example 12 Toxicity assessment of triclosan and its degradation products The toxicity of triclosan and its degradation products was comprehensively assessed using ECOSAR and TEST software. As shown in Table 1, regarding toxicity assessment of aquatic organisms, compared to the initial form, the acute and chronic toxicity of degradation products P1 and P2 to fish, water fleas, and green algae generally showed a decreasing trend, with their toxicity levels basically within the toxic range. The acute and chronic toxicity of degradation products P3 and P4 to water fleas decreased to non-toxic levels. However, the acute and chronic toxicity of P5 and P6 to water fleas rebounded, returning to toxic levels. Overall, P1 to P6 showed a significant reduction in toxicity compared to triclosan. Figure 12 The table shows the predicted acute toxicity (in rats) of triclosan and its degradation products. Specifically, the oral LD50 in rats for P1 is...50 No obvious change was observed for triclosan. The oral LD50 of degradation products P2-P6 in rats 50 The values were significantly lower than that of triclosan, indicating that the degradation products had lower acute toxicity (rats). In addition, the degradation products were less likely to be absorbed by the body, as indicated by the lower Kow values. ​ As shown in Table 1, the degradation products had lower acute and chronic toxicity than triclosan. In general, substances with higher bioaccumulation factors can produce amplification effects in high-trophic-level organisms through the food chain. Therefore, the health risks of triclosan to high-trophic-level organisms can be effectively reduced after degradation. The above results show that the potential threat to human health of triclosan can be significantly reduced after degradation by the visible light Fenton system catalyzed by PNM-101.

[0050] Table 1. Acute and chronic toxicity of triclosan and its degradation products evaluated by ECOSAR 2.2 (mg / L)

Claims

1. A method for preparing a bifunctional PABA-NH2-MIL-101(Fe) composite material (PNM-101) with a defect structure by combining solid phase microextraction and photo-Fenton degradation, characterized in that, The method comprises the following steps: FeCl3, NH2-BDC and p-aminobenzoic acid (PABA) are weighed and added into a centrifuge tube containing N,N-dimethylformamide (DMF). Then, the mixed solution is shaken and ultrasonicated until clear, and then transferred into a stainless steel high-pressure reaction kettle and heated at a temperature of 383 K. After the reaction kettle is cooled to room temperature, the product is washed with DMF and ethanol respectively, collected by centrifugal separation, and placed in a vacuum dryer at a temperature of 333 K. Finally, the obtained dark brown PNM-101 powder is ground and stored for use.

2. The method of claim 1, wherein, The amount of FeCl3 added is 480-490 mg, the amount of NH2-BDC added is 540-550 mg, and the amount of p-aminobenzoic acid added is 410-420 mg.

3. The method of claim 1, wherein, The heating time at a temperature of 383 K is 20-24 h, and the vacuum drying time at a temperature of 333 K is 10-12 h.

4. The solid phase microextraction with defect structure and photo-Fenton degradation bifunctional PNM-101 material according to claims 1-3, a PNM-101 coating fiber PNM-SSW is prepared, characterized in that, The method comprises the following steps: Stainless steel wire (SSW) was immersed in aqua regia for corrosion, washed with water and EtOH separately, dried naturally, and then immersed in the adhesive. The SSW with PNM-101 powder was taken out and adhered. The SSW coated with PNM-101 was placed in an oven for curing, and the operation was repeated 2-3 times. After the curing step was completed, the PNM-SSW was aged at 300-320 o C for 1-1.5 h to obtain PNM-SSW coated with PNM-101.

5. The PNM-101 coated fiber PNM-SSW according to claim 4, characterized in that, The adhesive is prepared by uniformly mixing and ultrasonically treating 1.2-1.5 g of plane sealant with 2.4-3.0 mL of toluene.

6. The PNM-101 coated fiber PNM-SSW according to claim 4, characterized in that, The temperature for curing the PNM-coated SSW in an oven is 110-120 °C, the first curing time is 25-30 min, and the second curing time is 3-3.5 h.

7. The PNM-101 material and PNM-101 coated fiber PNM-SSW according to claims 1-6, characterized in that, A solid phase microextraction (SPME) method is constructed, which specifically includes: (1) SPME procedure: Take the organic pollutant solution in a brown vial, add a magnetic stirrer, and then transfer it to a magnetic stirrer for stirring at room temperature. Then, the PNM-SSW fiber is pushed out of the fixed SPME device and immersed into the organic pollutant solution below the liquid surface for extraction, with an immersion length of 1.2-1.5 cm. After extraction, the PNM-SSW fiber is pulled back into the protective sleeve and transferred to the GC injection port for desorption; (2) SPME procedure during degradation: Take 1.0-1.2 mL of the degradation solution in a brown vial, dilute it with ultrapure water, and then transfer it to a magnetic stirrer for stirring at room temperature. The subsequent extraction is carried out according to the SPME procedure in (1). After extraction, the PNM-SSW fiber is pulled back into the protective sleeve, and then transferred to the GC-MS injection port for desorption, and the degradation solutions at different time periods are analyzed.

8. The solid-phase microextraction method according to claim 7, characterized in that, In step (1), the concentration of the organic pollutant mother liquor is 10-12 g / L, and the concentration of the organic pollutant solution obtained by dilution with ultrapure water is 1.0-1.2 mg / L.

9. The solid-phase microextraction method according to claim 7, characterized in that, In step (2), the amount of organic pollutant solution added is 10-12 mL.

10. The bifunctional PNM-101 material having a defective structure of solid phase microextraction and photo-Fenton degradation according to claim 1, wherein, Application in the fields of environmental protection and food detection.

11. Use according to claim 10, characterized in that, It can be used with photo-Fenton and solid phase microextraction to detect and degrade organic pollutants, including the enrichment detection and degradation of the organic pollutant trichlosan. It can be used with photo-Fenton and solid phase microextraction to detect and degrade organic pollutants, including the enrichment detection and degradation of the organic pollutant trichlosan.